Effects of neutrino mixing upon electron fraction in core collapse supernovae - Sáez, María Manuela (2017)
The inclusion of massive neutrinos affects the cross sections involved in the formation of heavy nuclei, modifying their abundances.Rapid neutron capture processes (r-process) are often associated with explosive events such as core-collapse supernovae. In this work we study the effects of active and sterile neutrino oscillations and interactions, upon the calculation of neutrino fluxes, the baryonic density and the electron fraction of the material. We have considered two different initial distribution functions of the neutrinos and different combinations of mixing parameters (including θ34 ≠ 0). We use the formalism of density matrices for the calculations and included the effects of neutrino oscillations, interactions with matter and self-neutrino interactions. We found that the interactions of the neutrinos with matter and with themselves change the electron fraction, affecting the onset of the r-process.